A Semi‐Conductive Copper–Organic Framework with Two Types of Photocatalytic Activity. (6th January 2016) - Wu, Zhi‐Lei; Wang, Chang‐Hong; Zhao, Bin; Dong, Jie; Lu, Feng; Wang, Wei‐Hua; Wang, Wei‐Chao; Wu, Guang‐Jun; Cui, Jian‐Zhong; Cheng, Peng
Abstract: Based on the newly designed ligand 4′‐(3, 5‐dicarboxyphenyl)‐4, 2′:6′, 4′′‐terpyridine (DCTP), a unique semi‐conductive 3D framework [Cu Ι Cu ΙΙ 2 (DCTP)2 ]NO3 ⋅1.5 DMF n (1 ) with a narrow band gap of 2.1 eV, was obtained and structurally characterized. DFT calculations with van de Waals correction employed to explore the electronic structure of1, clearly revealed its semi‐conductive behavior. Furthermore, we found that1 exhibits a superior band alignment with water to produce hydrogen and degrade organic pollutants. Without adding any photosensitizers, 1 displays an efficiently photocatalytic hydrogen production in water based on the photo‐generated electrons under UV/Vis light.1 also exhibits excellent photo‐degradation of methyl blue under visible‐light owing to the strong oxidization of excited holes. It is the first example of MOFs with doubly photocatalytic activities related to photo‐generated electrons and holes, respectively.